Feminicídio: a gravidade da violência de gênero e a necessária tutela da mulher - (:unkn) unknown (Universidade Federal do Pampa, 2025)
Violence against women, a topic that has gained prominence in recent years as a focus of study and research, is not only a topic of discussion for movements defending women's right to a peaceful life in society, but also violates human rights and impacts the environment as a whole, considering its impact on health and social development. This article addresses public policies to combat domestic violence against women. The research question is to ensure rights while maintaining a connection with women's family life, seeking to prevent femicide, which is so prevalent in women's lives. How can one survive in an environment that threatens one's own life? The objective of this study is to recognize the implications of violence suffered by women in the context of family and marital relationships, and to understand how it affects these women individually and collectively, as part of society, considering the current number of femicides. The study methods used were qualitative and descriptive bibliographical research of the phenomenological type, which sought to identify situations of violence, the number of feminicide cases, and social studies that have proven successful in combating this crime. By studying Law No. 11,340/2006 (Maria da Penha Law), which was enacted with the aim of definitively changing the punishment for aggressors of women with measures that guaranteed women the right to safety and freedom, a theoretical framework was presented that addressed violence against women as a historical construct in a society with patriarchal roots. The study addressed the different forms of sexual exploitation, where violence against women encompasses a range of other violations, including the safety of women and their families. Gender-based violence is discussed to understand this sexist practice that has existed since the beginnings of society, highlighting the need to more severely punish aggressors and abusers, thus seeking to eradicate gender-based violence. In conclusion, feminicide is analyzed as a social phenomenon that gained notoriety and as a way of highlighting the urgent need to save women's lives in the new society that was being established worldwide.
Femicide: the seriousness of gender-based violence and the necessary protection of women
Keywords: Feminicídio; Violência; Gênero; Direito da mulher; Femicide; Violence; Gender; Women's rights; CIENCIAS SOCIAIS APLICADAS